War - Petzel, Christopher; Thompson, Jim; Atwell, Philip G.; Lionsgate (Firm); Mosaic Media Group; Fierce Entertainment ([Santa Monica, California] : Lionsgate, 2007)
FBI Agent Jack Crawford is led to believe that his partner Tom Wynne and family are killed by the infamous and elusive assassin, Rogue. Jack becomes obsessed with revenge as his world unravels into a vortex of guilt and betrayal. Rogue eventually resurfaces to settle a score of his own, setting off a bloody crime war between Asian mob rivals Chang of the Triad's and Shiro the Yakuza boss. When Jack and Rogue finally come face to face, the ultimate truth of their pasts will be revealed
Title from title screen
Director of photography, Pierre Morel ; editor, Scott Richter ; music, Brian Tyler ; costume designer, Cynthia Ann Summers ; production designer, Chris August ; visual effects supervisors, Ray McIntyre, Jr., Mike Uguccioni
Cast: Devon Aoki, Jason Statham, Jet Li, John Lone, Luis Guzman, Matthew St. Patrick , Nicholas Elia, Sung Kang
DVD format
With optional Chinese or Malay subtitiles
Keywords: Assassins -- Drama; Revenge -- Drama; Betrayal -- Drama